Evolution of low-mode asymmetries introduced by x-ray P2 drive asymmetry during double shell implosions on the SG facility - Wang, Guanqiong; Li, Hang; Li, Xin; Li, Chenguang; Li, Xindong; Xu, Ruihua; Zhu, Ruidong; Li, Lulu; Zhang, Huasen; Zhao, Yingkui; Wang, Min; Guo, Liang; et al. (Nuclear fusion, 2024)
Double shell capsule can provide a potential low-convergence to fusion ignition at relatively low temperature (∼3 keV). One of the main sources of degrading double shell implosion performance is the low-mode asymmetries. Recently, the experiments on the evolution of low-mode asymmetries introduced by x-ray P2 drive asymmetry during double shell implosions were carried out on the SG facility, where the outer shell and inner shell shapes were measured through the backlit radiography, and the fuel shape near stagnation was measured by core x-ray self-emission imaging. The time-dependent x-ray flux symmetry was controlled by varying the inner cone fraction, defined as the ratio of the inner cone power to the total laser power, while keeping the drive temperature histories same across experiments. Both the hohlraum radiation and the capsule implosions were analyzed using a two-dimensional radiation-hydrodynamics code. Comparing the experimental radiographs and self-emission images to the simulations, it is found that the simulated outer shell, inner shell and hot spot shapes are in qualitative agreement with experiments, especially, the symmetry swings of the hot spot shape near stagnation are observed from both experimental and simulation results. Further, the effect of x-ray drive asymmetries on double shell implosion performance is preliminarily investigated using numerical simulations. We find that the azimuthal variations in radial velocity caused by drive asymmetries can generate azimuthal mass flow of the inner shell, thus kinetic energy of the inner shell would be not converted into fuel internal energy with high efficiency, and the mass-averaged ion temperature of the fuel at stagnation would be reduced.